Sarcopenia and Frailty Profile in the Elderly Community of Surabaya: A Descriptive Study - Novira Widajanti; Jusri Ichwani; Rwahita Satyawati Dharmanta; Hadiq Firdausi; Yudha Haryono; Erikavitri Yulianti; Stefanus Gunawan Kandinata; Meilia Wulandari; Rastita Widyasari; Viranti Ayu Adyanita; Nuri Indah Hapsanti; Diar Meitha Wardana; et al. (Interna Publishing, 2020)
Background: sarcopenia and frailty cause immobility, disability, neuromuscular disorders, and homeostatic balance failure syndrome, characterized by gait and balance abnormalities in the elderly, and an increasing prevalence worldwide. This further contributes to the elevated incidence of falls and fractures, hospitalization, immobilization, and even mortality, hence, a national-level study was conducted on the prevalence rates of sarcopenia and frailty in the elderly. Methods: this descriptive study used primary data of elderly people (n = 308) in Surabaya, Indonesia. Furthermore, the biopsychosocial data, weight loss, fatigue, and physical activity measurements were obtained through interviews, while handgrip strength, muscle mass, and physical performance (walking speed) were evaluated using instruments. Results: the median age of the subjects was 63 years (60-100 years), and 230 (74.7%) were women. In addition the prevalence rate of sarcopenia was 41.8% (in 86 [27.9%] women), while the prevalence rate of frailty was 36.7% (in 16 [5.2%] men and 97 [31.5%] women). Conclusion: the prevalence of sarcopenia and frailty in the elderly is significantly high, thus, it is expected that this study results are used as a basis for subsequent research, especially to determine the sarcopenia cut-off, in accordance with Indonesian sociodemography.